Microwave-assisted asymmetric Diels-Alder reaction using chiral auxiliaries derived from biomass - Sarotti, Ariel Marcelo (2011)
Microwave-assisted asymmetric Diels-Alder reactions using levoglucosenone-derived chiral auxiliaries have been investigated. The cycloaddition reaction between the corresponding chiral acrylate and cyclopentadiene showed important rate enhancements under microwave irradiation compared to conventional heating conditions, whereas the yields and diastereoselectivities were not significantly affected.